Characterization antibacterial constituent from Ficus deltoideus Jack leaves - Suryati; Hazli Nurdin; Dachriyanus; Md Nordin Hj Lajis (Universitas Gadjah Mada, 2010)
An antibacterial constituent, has been isolated from Ficus deltoideus Jack leaves. Based on spectroscopic data (IR, 1H-NMR, 13 C NMR 1D and 2D and MS), the structure of this compound was identified as Olean-12en-3β-ol, (β-amyrin), C30H50O. This compound showed antibacterial activities against E. coli, B. subtilis and S. aureus. The minimum inhibition concentration (MIC) agains E. coli, B. subtilisand S. aureusare 230, 380 and 460 (µg/mL) respectively.